2004
DOI: 10.1128/iai.72.3.1333-1340.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Virulence-Associated Genes via Genome Analysis of Hypothetical Genes

Abstract: The sequencing of bacterial genomes has opened new perspectives for identification of targets for treatment of infectious diseases. We have identified a set of novel virulence-associated genes (vag genes) by comparing the genome sequences of six human pathogens that are known to cause persistent or chronic infections in humans: Yersinia pestis, Neisseria gonorrhoeae, Helicobacter pylori, Borrelia burgdorferi, Streptococcus pneumoniae, and Treponema pallidum. This comparison was limited to genes annotated as hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 55 publications
(46 reference statements)
1
30
1
Order By: Relevance
“…The effect of the two factors is cumulative, and we interpret these observations to mean that the termination machinery can tolerate the effect either of the presence of Thr rather than Ala/Ser or the lack of Gln methylation but that the accumulated effect of both factors reduces termination efficiency at some stop codons to a level incompatible with cell growth. For reasons that remain to be determined, PrmC in Yersinia pseudotuberculosis is required for virulence, although not for growth in rich liquid media (32).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the two factors is cumulative, and we interpret these observations to mean that the termination machinery can tolerate the effect either of the presence of Thr rather than Ala/Ser or the lack of Gln methylation but that the accumulated effect of both factors reduces termination efficiency at some stop codons to a level incompatible with cell growth. For reasons that remain to be determined, PrmC in Yersinia pseudotuberculosis is required for virulence, although not for growth in rich liquid media (32).…”
Section: Discussionmentioning
confidence: 99%
“…A requirement for methylation has been demonstrated in Y. pseudotuberculosis, where an insertion mutant deficient in the VagH protein is avirulent in mice (Garbom et al, 2004). In Y. pseudotuberculosis, the VagH protein is homologous to the E. coli HemK protein (Garbom et al, 2007), an N 5 -methyltransferase (Heurgué-Hamard et al, 2002;Nakahigashi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of glycolipids has been shown to be essential for Mycobacterium avium virulence in mice (Krzywinska et al, 2005), while methylation of proteins has been shown to alter the antigenicity of the outer-membrane protein OmpB from Rickettsia typhi (Chao et al, 2008), and to alter both the antigenicity of and the host T cell-mediated immune response against the heparin-binding haemagglutinin from Mycobacterium tuberculosis Temmerman et al, 2004). In addition, methylation has been demonstrated to be essential for functional type III secretion, and thus virulence, in Yersinia pseudotuberculosis (Garbom et al, 2004(Garbom et al, , 2007, and methylation of the surface protein OmpB in Rickettsia prowazaki has been suggested to be central to the pathogenesis of that bacterium (Chao et al, 2004(Chao et al, , 2007. Collectively, these investigations highlight the importance of methylation of outer-membrane surface components in bacterial virulence.…”
Section: Introductionmentioning
confidence: 99%
“…Va-iv-15 encodes MesJ that is involved in cell division. With a bioinformatic approach, MesJ homologue was identified and designated as virulence-associated genes in E. coli (Garbom et al 2004). It needs further study to determine whether V. anguillarum YaeT and MesJ are virulence factors.…”
Section: Discussionmentioning
confidence: 99%